Towards an Integration of Immigration and Customs Agency in Indonesia: A Step-by-Step Process - Ridwan Arifin; Intan Nurkumalawati (Universitas Muhammadiyah Tangerang, 2021)
Some challenges appear in this issue that the Indonesian border agencies indicate weaknesses in coordination, fragmented policy instruments, and disputes in implementing laws. There has little evidence in the previous study about the integration of border agencies in Indonesia and perspectives on the establishment of immigration and customs agencies. The questions may arise how important is the integrated border agencies is in the reform agenda in public sectors and bureaucracy from the perspectives of border officers. This study is to figure out the perspectives of border officers on the integration of two border authorities in Indonesia and what the ideal integration should be. This paper provides solutions for some issues of border protection in Indonesia with survey research and a step-by-step process of integration. This paper finds most immigration and customs officers at border controls exposed the importance of an integration initiative between the Directorate General of Immigration (DGI) and Directorate General of Customs and Excise (DGCE) in Indonesia through the Integrated Border Management (IBM) strategy. Therefore, initiating the integration of institutions between the Directorate General of Immigration and Directorate General of Customs and Excise, such as ICA Singapore or ABF Australia is more ideal border agencies rather than a joint-task force.Permasalahan di instansi pemerintah yang menangani perbatasan di Indonesia masih terjadi seperti adanya kelemahan dalam koordinasi, terdapat instrumen kebijakan yang terpisah-pisah, dan terjadinya tumpang tindih dalam penegakan hukum. Penelitian sebelumnya tentang inisiasi integrasi instansi di perbatasan Indonesia masih sangat minim terutama penggabungan dua otoritas perbatasan seperti imigrasi dan bea cukai. Pertanyannya adalah seberapa penting penggabungan dua otoritas perbatasan tersebut dalam rangka agenda reformasi birokrasi di sektor publik dari perspektif petugas perbatasan. Studi ini menggunakan penelitian survei dengan melihat perspektif dari petugas perbatasan terhadap integrasi dua otoritas perbatasan di Indonesia dan bagaimana seharusnya bentuk ideal penggabungan tersebut. Hasil penelitian menunjukkan bahwa sebagian besar petugas imigrasi dan kepabeanan menyatakan sangat setuju dengan inisiasi penggabungan Direktorat Jenderal Imigrasi dan Direktorat Jenderal Bea dan Cukai dengan menerapkan strategi manajemen perbatasan terintegrasi (IBM). Integrasi dua tersebut dalam bentuk badan baru seperti ICA Singapore atau ABF Australia ketimbang tim atau gugus tugas yang bersifat sementara